Scientific Opinion on the substantiation of a health claim related to fat-free yogurts and fermented milks with live yogurt cultures complying with the specifications ?fat free?, ?low in sugars?, ?high protein?, ?source of calcium? and ?source of vitamin D? for nutrition claims and maintenance of lean body mass in the context of an energy-restricted diet pursuant to Article 13.5 of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal, 2015)
Following an application from Federación Nacional de Industrias Lácteas (FeNIL), submitted pursuant to Article 13.5 of Regulation (EC) No 1924/2006 via the Competent Authority of Spain, the Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to fat-free yogurts and fermented milks with live yogurt cultures complying with the specifications “fat free”, “low in sugars”, “high protein”, “source of calcium” and “source of vitamin D” for nutrition claims and maintenance of lean body mass in the context of an energy-restricted diet. The Panel considers that the food that is the subject of the claim, fat-free yogurts and fermented milks complying with the specifications “fat free”, “low in sugars”, “high protein”, “source of calcium” and “source of vitamin D” for nutrition claims, is sufficiently characterised. The Panel considers that maintenance of lean body mass in the context of an energy-restricted diet is a beneficial physiological effect. No human intervention studies from which conclusions could be drawn for the scientific substantiation of the claim were provided. The Panel concludes that a cause and effect relationship has not been established between the consumption of fat-free yogurts and fermented milks with live yogurt cultures complying with the specifications “fat free”, “low in sugars”, “high protein”, “source of calcium” and “source of vitamin D” for nutrition claims and maintenance of lean body mass in the context of an energy-restricted diet.